"solve ~ (y^{\\prime})^2= \\frac{1-y^2}{1-x^2}, ~ y(1)=\\frac{1}{2}, \\\\ \ny^{\\prime} = \\pm\\sqrt{\\frac{1-y^2}{1-x^2}}\\\\\n\\frac{dy}{\\sqrt{1-y^2}}=\\pm\\frac{dx}{\\sqrt{1-x^2}}\\\\\n\\int\\frac{dy}{\\sqrt{1-y^2}}=\\pm\\int\\frac{dx}{\\sqrt{1-x^2}}\\\\\n\\ln{|y+\\sqrt{1-y^2}|}=\\pm\\ln{|x+\\sqrt{1-x^2}|} +\\ln|c| \\\\\n\\left[ \n \\begin{gathered} \n y+\\sqrt{1-y^2}=c(x+\\sqrt{1-x^2}),\\\\\n y+\\sqrt{1-y^2}=\\frac{c}{(x+\\sqrt{1-x^2})}.\\\\\n \\end{gathered} \n\\right.\\\\\ny(1)=\\frac{1}{2}.\\\\\n\\left[ \n \\begin{gathered} \n \\frac{1}{2}+\\sqrt{1-(\\frac{1}{2})^2}=c(1+\\sqrt{1-1^2}),\\\\\n \\frac{1}{2}+\\sqrt{1-(\\frac{1}{2})^2}=\\frac{c}{(1+\\sqrt{1-1^2})}.\\\\\n \\end{gathered} \n\\right.\\\\\n\\left[ \n \\begin{gathered} \n \\frac{1}{2}+\\sqrt{\\frac{3}{4}}=c,\\\\\n \\frac{1}{2}+\\sqrt{\\frac{3}{4}}=c.\\\\\n \\end{gathered} \n\\right.\\\\\nc=\\frac{1+\\sqrt{3}}{2}\\\\\nanswer: \\\\ \\left[ \n \\begin{gathered} \n y+\\sqrt{1-y^2}=\\frac{(1+\\sqrt{3})}{2}(x+\\sqrt{1-x^2}),\\\\\n y+\\sqrt{1-y^2}=\\frac{1+\\sqrt{3}}{2(x+\\sqrt{1-x^2})}.\\\\\n \\end{gathered} \n\\right.\\\\"
Comments
Leave a comment